(untitled) (Research, Society and Development, 2022)
The study aimed to analyze the prevalence of recent mothers, which use the Oral Health Services in the Brazilian Unified Health Systems (OHS/BUHS) during pregnancy and received guidelines to their oral health and baby. This was a cross-sectional study and 223 recent mothers were interviewed. Poisson regression models were used in the multivariate analysis. 48% of the recent mothers use the OHS/BUHS during pregnancy, 31% received guidelines to their oral health and less than 15% received guidelines of the oral health to their baby. The recent mothers, who were referred to appointments with the dentist during the pregnancy increased by 39% [Prevalence Ratio (PR) 1.39; Confidence Interval (CI) 95% 1.27-1.53] likelihood of using the OHS/BUHS and 27% (PR1.27; CI 95% 1.17-1.39) to receive guidelines to their oral health (vs no receive). Recent mothers should be referred to appointments with the dentist to promote the use of the oral health services during the pregnancy and received guidelines to their oral health and baby. Greater collaboration among professionals will qualify maternal-infant oral health.